1984
DOI: 10.1029/jc089ic06p10431
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and effects of long waves in the equatorial Pacific

Abstract: Data from 20 satellite‐tracked drifting buoys deployed in the eastern equatorial Pacific Ocean during the summer of 1979 were used to investigate the nature, effects, and energetics of currents associated with cusp‐shaped long waves observed in satellite IR imagery of the sea surface during all except El Nino years. It is shown that the long waves are associated with a vigorous pattern of mesoscale eddies lying primarily between the equator and 7°N. The spatial structure of the eddy kinetic energy closely rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
166
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 18 publications
17
166
0
Order By: Relevance
“…[13] Surface velocity drifter observations in the tropical Pacific started in 1978 [Hansen and Paul, 1984] with the objective of mapping the surface currents from local to regional scales with accuracy that is only possible with this type of instrument [Griffa et al, 2007]. In the last 4 years, the number of drifter observations has increased sufficiently to obtain a statistically robust representation of the WCS basin surface circulation.…”
Section: Methodsmentioning
confidence: 99%
“…[13] Surface velocity drifter observations in the tropical Pacific started in 1978 [Hansen and Paul, 1984] with the objective of mapping the surface currents from local to regional scales with accuracy that is only possible with this type of instrument [Griffa et al, 2007]. In the last 4 years, the number of drifter observations has increased sufficiently to obtain a statistically robust representation of the WCS basin surface circulation.…”
Section: Methodsmentioning
confidence: 99%
“…It is not possible with the current design to determine the eddy momentum flux divergence of the TIW and it is difficult to determine their eddy heat flux divergence, both of which are of major importance for the equatorial circulation (Hansen and Paul (1984) and Bryden and Brady (1989)). It takes, however, only minor additions to PIRATA to correct for this.…”
Section: Observing the Tropical Instability Waves In The Atlantic Oceanmentioning
confidence: 99%
“…Their period is between 20 and 40 days and their wavelength is of the order of 1000km (Legeckis (1977) and Weisberg and Weingartner (1988)). Hansen and Paul (1984) and Bryden and Brady (1989) show that the equatorward heat flux of the TIW exceeds the atmospheric heat flux at the equator. Thus, the position and strength of the equatorial cold tongue is sensitive to the structure of the TIW.…”
Section: Introductionmentioning
confidence: 99%
“…They also show that the zonal temperature advection due to the TIWs is as important as the meridional one. On the other hand, the study of Hansen and Paul (1984) in a similar region concluded that the zonal eddy heat flux is small. They used datasets which had been averaged over several days so this may explain why their analysis came to this conclusion.…”
Section: Discussionmentioning
confidence: 99%